Answer:
i can't doesn't show picture sorry.
Step-by-step explanation:
Answer:
Step-by-step explanation:
Hello !
cos (a+b) = cos a cos b - sin a sin b
sin (a+b) = sin a cos b + sin b cos a
cos (a+b+c) = cos (a+(b+c))
cos (a+b+c) = cos a cos (b+c) - sin a sin (b+c)
cos (a+b+c) = cos a (cos b cos c - sin b sin c) - sin a (sin b cos c + sin c cos b)
cos (a+b+c)=cos a cos b cos c - cos a sin b sin c - sin a sin b cos c - sin a cos b sin c
Answer:
X= 2.
X= -5.
Step-by-step explanation:
Hope it was helpful ;)